Employer branding of the pharmaceutical companies as a tool for recruitment students and recent graduates for business-related positions - Strakhova, Alla (2020)
The aim of this thesis is to define suggestions and recommendations that can help specific companies of the pharmaceutical industry to make the use of communication channels more efficient in order to spread the awareness of the employer brand towards the target group, represented by students and recent graduates. The work focuses mainly on the use and effectiveness of individual external communication channels. The thesis consists of two parts – theoretical and analytical. The first theoretical part covers marketing approach to human resources, the concept of Employer Branding and describes HR marketing communication tools. It is followed by the analytical part which is dedicated to the Czech labour market and pharma sector analysis. It is then completed by the evaluation of the corresponding questionnaire and consequently concluded by the appropriate recommendations.